Proposing a sales performance motivational framework for B2B sellers in services firms - Rocío Rodríguez; Mornay Roberts-Lombard; Nils M. Høgevold; Göran Svensson (European Research on Management and Business Economics (ERMBE), 2024)
This study tests a framework of business-to-business (B2B) sellers' sales performance motivations in services firms. An exploratory-descriptive research design was used and data was collected from 389 respondents working in the services-orientated business sector of Norway. The study's results verify that B2B service sales are complex contexts and situations for B2B seller services firms and their B2B customers to handle. Many elements are required to reach a final deal. Therefore, services firms must maintain seller motivation throughout the B2B services sales process, which is usually hard and may involve psychological wear-out. Consequently, this study examines and verifies an important area of sales performance indicators, namely B2B sellers' motivations in services firms, and explains B2B sellers' intrinsic and extrinsic motivations.
Keywords: M2; M3; 650; Cognitive choice; Goal orientation; Intrinsic motivation; Outcome productivity